Unraveling the enigma: a case series of human pentastomiasis encounters - Said, Abdul Hadi; Mansor, Noor Emilia Emira; Mohd Yusof, Mubarak (Universiti Kuala Lumpur, Royal College of Medicine Perak, 2024)
Pentastomiasis is a zoonotic parasitic disease caused by pentastome parasites, typically reported in Africa, the Middle East, and Southeast Asia. The definitive hosts of Armillifer spp. (a subclass of pentastomes) are snakes, lizards, and other reptiles. Humans acquire the infestation incidentally by consuming uncooked, infected snake meat or drinking water contaminated with pentastome ova. We report two cases of human pentastomiasis, an uncommon condition today. This case report aims to provide the latest updates on human pentastomiasis, particularly in Malaysia, and promote awareness among primary healthcare providers.